Magnitude and associated factors of unmet need for family planning among reproductive-aged women in Ethiopia: An umbrella review. - Mulat Ayele; Gizachew Yilak; Abebaw Alamrew; Eyob Shitie Lake; Befkad Derese Tilahun (PLoS ONE)
Introduction The World Health Organization defines women with an unmet need for family planning as individuals who are fecund, sexually active, and wanting to either to limit childbirth or postpone their next birth but are not utilizing any form of contraception. Previous meta-analyses and systematic reviews have focused on this topic, but no comprehensive summary of the evidence was available. Therefore, the aim of this study was to provide a summary of the findings on the unmet need for family planning among reproductive-aged women in Ethiopia. Method A search was conducted in PubMed, Google Scholar, CINAHL, Scopus, Cochrane Library, and RESEARCH 4 LIFE including Hinari, to identify relevant systematic reviews and meta-analyses of studies on the prevalence and determinants of the unmet need for family planning in Ethiopia. The methodological quality of the included studies was assessed using the Assessment of Multiple Systematic Reviews tool, and the estimates were pooled using a random-effects meta-analysis model. Results The umbrella review included five studies with a total of 56,169 reproductive-aged women. The pooled prevalence of unmet need for family planning was found to be 27.44% (95% CI: 22.32-32.55), with the heterogeneity index (I square = 99.45%, P = 0.000). Failure to discuss with her partner about family planning methods (OR: 2.90, 95% CI: 1.81, 4.00), being illiterate (OR: 2.17, 95% CI: 1.42, 2.92), age at first marriage (OR: 1.37, 95% CI: 1.30, 1.44), and educational status of woman's partner (OR: 2.61, 95% CI: 0.83, 4.40) were the factors significantly and positively associated with unmet needs for family planning. Conclusion The study concludes that the unmet need for family planning in Ethiopia is a significant issue that can be addressed through increasing the educational levels of women and their partners, promoting open discussions about family planning, and preventing early marriages. Collaboration between families, school administrators, and healthcare providers is essential to mitigating this problem.